1986
DOI: 10.1126/science.3726547
|View full text |Cite
|
Sign up to set email alerts
|

Near-Total Glutathione Depletion and Age-Specific Cataracts Induced by Buthionine Sulfoximine in Mice

Abstract: The specific inhibitor of glutathione biosynthesis, L-buthionine sulfoximine (L-BSO), although relatively nontoxic in adult mice, induces severe glutathione depletion and age-specific pathological changes when repeatedly administered to male suckling mice. Dense cataracts developed when mice aged 9 to 12 days were given a series of injections of L-BSO, despite excellent survival and the absence of other significant long-term effects. By contrast, similar treatment of mice aged 14 to 17 days, although slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…When pregnant mice were given BSO at different periods during gestation (i.e., from days 6-10, 9-13, or [15][16][17][18][19], cataracts were found in the offspring only after BSO was given on days 15-19. This period corresponds to that in which much of fetal eye development occurs (31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When pregnant mice were given BSO at different periods during gestation (i.e., from days 6-10, 9-13, or [15][16][17][18][19], cataracts were found in the offspring only after BSO was given on days 15-19. This period corresponds to that in which much of fetal eye development occurs (31).…”
Section: Resultsmentioning
confidence: 99%
“…Administration of buthionine sulfoximine (BSO) (11), an effective inhibitor of -t-glutamylcysteine synthetase (the enzyme that catalyzes the first step in the biosynthesis of GSH), to mice and rats leads to markedly decreased levels of GSH in many tissues (12)(13)(14). Administration of BSO to mice 9-12 days old leads to low levels of lens GSH and to cataract formation (15). These and earlier findings suggest that there is a causal relationship between decreased levels of GSH and the formation of cataracts, but it is conceivable that the effect of BSO is mediated through another mechanism.…”
mentioning
confidence: 99%
“…Major developmental changes also occur at this time in liver and brain. GSH deficiency in adult mice leads to lamellar body abnormalities (28) and in newborn rats leads to a decreased number of lamellar bodies and reduced amounts of intraalveolar tubular myelin, which is secreted by the lamellar bodies ( Fig. 1 a and b).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial degeneration may be ascribed to accumulation of hydrogen peroxide and consequent oxidative damage; a significant fraction of the oxygen used by mitochondria, which do not contain catalase, is normally converted to hydrogen peroxide (24)(25)(26)(27). The finding that treatment of newborn mice with BSO produced cataracts (28) led to studies on newborn mice and rats in which it was found that cataracts, which are formed after giving a small dose of BSO, may be prevented by giving GSH monoester (29). BSO is poorly transported into the brains of adult animals and thus has only a small effect on the brain GSH level (30,31).…”
mentioning
confidence: 99%
“…Thus the cell's reducing powers ultimately depend largely on the production of NADPH by the glycolytic pentose phosphate shunt. Glutathione reserves can be depleted by oxidative stress (Maellaro et al, 1990) and such depletion in the brain can cause neurological deficits (Calvin et al, 1986). The brainstem has a relatively low glutathione content and a high content of mixed function oxidase.…”
Section: Mitigation Of Cerebral Oxidative Stressmentioning
confidence: 99%